2015
DOI: 10.1039/c5mb00470e
|View full text |Cite
|
Sign up to set email alerts
|

Potential of serum metabolites for diagnosing post-stroke cognitive impairment

Abstract: Cognitive impairment commonly accompanies clinical syndromes associated with stroke. The identification of laboratory markers of post-stroke cognitive impairment (PSCI) may help detect patients at increased risk of cognitive deterioration and determine the appropriate treatment regimes. A non-targeted metabolomics approach based on ultra-high performance liquid chromatography coupled with Q-TOF mass spectrometry was applied to study PSCI. The stroke patients were significantly distinguishable from the healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 59 publications
5
59
1
Order By: Relevance
“…The application of metabolomic tools to study brain diseases have greatly enhanced our understanding of different pathologies, for example; we demonstrated the upregulation of the ceramide "Cer(d18:0/18:0)" and phosphocreatine following transient ischemia-reperfusion in mice using a mass spectrometric imaging approach 15 . Several studies have highlighted an array of small molecules, amino acids and lipids that were linked to stroke severity, progression or post-stroke cognitive deficits [23][24][25] . Moreover, linoleic acid…”
mentioning
confidence: 99%
“…The application of metabolomic tools to study brain diseases have greatly enhanced our understanding of different pathologies, for example; we demonstrated the upregulation of the ceramide "Cer(d18:0/18:0)" and phosphocreatine following transient ischemia-reperfusion in mice using a mass spectrometric imaging approach 15 . Several studies have highlighted an array of small molecules, amino acids and lipids that were linked to stroke severity, progression or post-stroke cognitive deficits [23][24][25] . Moreover, linoleic acid…”
mentioning
confidence: 99%
“…These results were confirmed by Moretti and colleagues, who found a higher homocysteine level in VaD patients, but also a significantly vitamin D deficiency and low levels of folate [16], as well as in elderly patients with fatigue [56]. Liu and co-workers suggested a biomarker panel of three metabolites (glutamine, kynurenine, and lysophosphatidylcholines) to predict the post-stroke cognitive impairment [12].…”
Section: Serummentioning
confidence: 59%
“…Therefore, a total of 46 papers were eventually included in this study ( Figure 1) and the main findings are summarized in Table 1. More in details, 8 studies deal with serum biomarkers [9][10][11][12][13][14][15][16], 10 with cerebrospinal fluid (CSF) [17][18][19][20][21][22][23][24][25][26], 4 with neuroimaging [27][28][29][30], 6 with histopathology [31][32][33][34][35][36], and 14 with transcranial magnetic stimulation (TMS) [37][38][39][40][41][42][43][44][45][46][47][48][49][50]; 4 studies included more than one technique: one studied both serum and CSF markers [51], two both serum and neuroimaging [52,53], and one both CSF and neuroimaging…”
Section: Resultsmentioning
confidence: 99%
“…None of these studies, however, have identified and characterized in vivo ECTP plasma metabolites. Apart from these studies, a body of previous work has utilized LC/MS‐based metabolomic approaches to support the treatment of a variety of neuropsychiatric disorders including stroke, bipolar disorder, and autism . Very few studies, however, have ECTP blood plasma concentration and response prediction .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these studies, a body of previous work has utilized LC/MS-based metabolomic approaches to support the treatment of a variety of neuropsychiatric disorders including stroke, bipolar disorder, and autism. [24][25][26][27][28] Very few studies, however, have ECTP blood plasma concentration and response prediction. 29,30 One previous study demonstrated that early improvement and ECTP serum concentration could be used to predict the effectiveness of antidepressant drug response in MDD patients.…”
mentioning
confidence: 99%